Business Innovation of the Local Snacks Industry in Jember City, East Java - Kantun, Sri; Sedyati, Retna Ngesti; Tiara, Tiara; Mujib, Muhammad Asyroful; Triyanto, Jefri Rieski (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This descriptive qualitative research describes the findings in the field of innovation carried out by the souvenir home industry in Jember Regency, which includes product innovation, service/marketing innovation, and process innovation. This research was conducted in May 2022, with the target subjects being the owners of the local snacks industry. This study uses interviews, observation, and documentation techniques to obtain data on development of the number of local snacks industries, turnover, and regulations related to food/processing companies. The results indicate that the COVID-19 pandemic has threatened business continuity in the three local snacks industries due to decreased revenue and product sales and delays in product marketing and distribution. This indicates that product innovation can lead to easier production; product innovation is also important for effective marketing and, consequently, the company's financial performance. Therefore, business innovation needs to be done in the context of business development, especially local snacks products, so that they can compete with other local snacks household industries.